2013
DOI: 10.1016/j.ceca.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

9-Phenanthrol and flufenamic acid inhibit calcium oscillations in HL-1 mouse cardiomyocytes

Abstract: It is well established that intracellular calcium ([Ca2+]i) controls the inotropic state of the myocardium, and evidence mounts that a “Ca2+ clock” controls the chronotropic state of the heart. Recent findings describe a calcium-activated nonselective cation channel (NSCCa) in various cardiac preparations sharing hallmark characteristics of the Transient Receptor Potential Melastatin 4, (TRPM4). TRPM4 is functionally expressed throughout the heart and has been implicated as a NSCCa that mediates membrane depol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
(79 reference statements)
0
23
1
Order By: Relevance
“…The results summarized earlier indicate that 9‐phenanthrol acts in sinoatrial node cells to directly slow the diastolic depolarization through inhibiton of TRPM4 channels. However, a study conducted on the HL‐1 cell line derived from mouse atrial cells revealed that 9‐phenanthrol also modulates cytoplasmic calcium oscillations (Burt et al ., ). HL‐1 cells are derived from atrial cardiomyocytes, but not specifically sinoatrial node cells, and they acquire properties similar to those of pacemaker cells and develop free beating activity, with intracellular calcium oscillations being present in about 40% of the cells (Wondergem et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…The results summarized earlier indicate that 9‐phenanthrol acts in sinoatrial node cells to directly slow the diastolic depolarization through inhibiton of TRPM4 channels. However, a study conducted on the HL‐1 cell line derived from mouse atrial cells revealed that 9‐phenanthrol also modulates cytoplasmic calcium oscillations (Burt et al ., ). HL‐1 cells are derived from atrial cardiomyocytes, but not specifically sinoatrial node cells, and they acquire properties similar to those of pacemaker cells and develop free beating activity, with intracellular calcium oscillations being present in about 40% of the cells (Wondergem et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…HL‐1 cells are derived from atrial cardiomyocytes, but not specifically sinoatrial node cells, and they acquire properties similar to those of pacemaker cells and develop free beating activity, with intracellular calcium oscillations being present in about 40% of the cells (Wondergem et al ., ). Fluorescent Ca 2+ recordings using Fura‐2 revealed that 10 −5 mol·L −1 9‐phenanthrol abolishes these Ca 2+ oscillations leading to a transient increase in cytoplasmic Ca 2+ , attributed to the release of Ca 2+ from an intracellular pool different from the sarcoplasmic reticulum and thus, is most likely to be mitochondrial Ca 2+ (Burt et al ., ). These Ca 2+ oscillations could participate in the spontaneous activity, since the application of 10 −5 mol·L −1 9‐phenanthrol in cell‐attached recordings from HL‐1 cells abolished the depolarizing inward ionic currents that contribute to the slow diastolic depolarization (Burt et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…9‐Phenanthrol (10–100 μM) has also been reported to mitigate calcium oscillation in HL‐1 mouse cardiomyocytes (Burt et al, ) and terminate burst firing in a neuronal system (Mrejeru et al, ), and again these may partially attributed to sodium current inhibition.…”
Section: Discussionmentioning
confidence: 99%